Position control of pneumatic actuator using an enhancement of NPID controller based on the characteristic of rate variation nonlinear gain - Syed Najib , Syed Salim; Mohd Fua'ad , Rahmat; Ahmad 'Athif , Mohd Faudzi; Zool Hilmi, Ismail (International Journal of Advanced Manufacturing Technology, 2014)
This paper presents an enhancement of nonlinear proportional-integral-derivative (PID) controller for pneumatic positioning system by utilizing the characteristic of rate variation nonlinear gain known as multi-rate nonlinear PID controller. The proposed technique is designed and implemented to a variably loaded pneumatic actuator. To utilize the rate variation of nonlinear gain, fuzzy logic technique was used in determining the appropriate rate selection to produce a rapid response without generating a significant overshoot. Simulation and experimental tests are conducted with different kinds of input, namely, step, sinusoidal, and random wave forms to evaluate the performance of the proposed technique. The results have proven as a novel initiative at examining and identifying the characteristic based on a new proposal controller resulting from NPID controller where the transient response has improved by a factor of 7 times greater than the previous NPID technique. Moreover, the performance of pneumatic positioning system is remarkably good when operated under the variable load condition.